Analysis and assessment of water quality parameters at Nhu Y river - Nguyễn , Minh Kỳ (Journal of Technical Education Science, 2013)
The article provides the results of surface water quality of Nhu Y River in dry season. The research was carried out at 5 sites in 2012 and the results have shown the general development situation of water resource quality of Nhu Y River by parameters such as DO, BOD5, COD, NO3-, PO43-. Almost of DO content in stations reached the value of B1 and B2 in QCVN 08:2008/BTNMT standard. The research has also shown BOD5 and COD content in ranges of 7.2 mg/L (S4, May) to 13.4 mg/L (S1, May) and 8.1 mg/L (S1, May) to 17.2 mg/L (S2, May), respectively. The value of NO3- content in Nhu Y river has least average in March (0.16 mg/L, S1) and largest average in May (0.54 mg/L, S3). To PO43- content, existed lowest monitoring value at station S1 (0.002 mg/L, June) and highest value in March at station S3 (0.220 mg/L). In addition, result of correlation analysis between BOD5 and COD with coefficient is 0.599 at the 0.01 level.